Economic impact of the clinical pharmacist interventions in the pediatric intensive care unit - Bruna de Melo Menezes; Francieli Zanella Lazaretto; Lucélia Hernandes Lima; Karin Hepp Schwambach; Carine Raquel Blatt (São Paulo State University (UNESP), 2021)
Introduction: The clinical pharmacist in the intensive care unit is involved in the aspects of patient safety, technical guidance for the team care and cost saving with rational use of medicines. Objective: This study aims to estimate the cost saving with of the clinical pharmacist interventions in the pediatric intensive care unit (PICU). Methods: This was a retrospective, observational study. The cost saving was measured over three months based on (1) Clinical pharmacist interventions from the prescriptions analysis. (2) Individualized doses of four antibiotics. (3) Comparison of drugs dispensing system between the period before and after the decentralization of pharmacy services. The main outcome measure is costs saving with strategic planning for the rational use of medicines, based on local reality. Results: 173 clinical pharmacist interventions were carried out, from 13 interventions we could calculated the economic impact, resulting in an estimate cost saving of the US$ 633.38/year. Cost saving from individualized doses of four antimicrobials was US$ 8,754.46/year. The decentralization of the pharmacy service resulted in a cost saving of US$ 28,770.52/year. Conclusion: The clinical pharmacist in the pediatric intensive care unit results in cost saving. Clinical pharmacist interventions, antimicrobials individualized doses and decentralization of pharmacy services reduce costs in the hospital.